Bullying Prevention Counseling for Students High School - Miftahul Zannah Raharjo Putri; Anisa Natalia; Asrina Yeni; Evi Martina; Ridariah; Yuli Puspita; Riswandi; Muhammad Nurwahidin (Program Doktor Pendidikan FKIP Universitas Lampung, 2026)
Bullying is a form of violence that still often occurs in schools and has a negative impact on the psychological, social, and academic development of students. This Community Service (PkM) activity aims to increase students' knowledge and awareness of bullying prevention through counseling, group discussions, educational video screenings, and quizzes at SMAN H. This activity was carried out in response to the high incidence of bullying among adolescents, as reported in various studies, including the findings of Bachri et al., and linked to extreme cases resulting from psychological pressure on bullying victims. The results of the activity showed an increase in students' understanding of the definition, forms, causes, and effects of bullying, accompanied by positive attitude changes such as increased empathy and courage to report cases of bullying. Guidance counselors and homeroom teachers also benefited from learning strategies for preventing and handling bullying. This activity was effective in building a safe and anti-bullying school culture and is recommended to be implemented on an ongoing basis